Student´s perceptions of the use of traditional and active learning strategies in the classroom: findings from a case study - Fernandes, Sandra (2021)
(...) The high levels of absenteeism in class, the lack of interest by the students and the assessment results were some of the main reasons that lead the course lecturer to implement a set of changes in the curricular unit, in the following academic year. These changes included the use of traditional and non-traditional teaching and assessment practices in the classroom such as flipped classroom, team-based learning, brainstorming, lectures, demonstration, gallery walk, review of videos and case studies. To evaluate student satisfaction with these changes, feedback was collected from students, at the end of the semester, through a questionnaire with 26 questions on a five-level Likert scale. The topics addressed in the questionnaire included the following dimensions: teacher performance, teaching and assessment methods, competences development and overall satisfaction with the curricular unit. The participants in the study were 94 students enrolled in the curricular Management Information Systems rd year study plan of the Management degree programme at Portucalense University, Porto, Portugal. This curricular unit is mandatory and has more than one hundred students enrolled every year. The curricular unit ceptions reveal a positive view of the changes implemented, as lectures were considered more interesting and there was more active engagement by the students. (...)